The impact of soil tillage systems on soybean yield capacity - Chaika, T.; Lohvynenko, V.; Pshenyshnyi, A. (Scientific Progress & Innovations, 2023)
Modern soil tillage systems have to ensure both crop yield capacity and economic efficiency as well as ecological consequences to the environment. The article is aimed at studying the impact of different soil tillage systems on soybean varieties’ yield capacity. The research was conducted during 2021–2023 on the territory of Hlobyne district in Poltava region using the traditional plowing, deep loosening, and no-till. Modern soybean varieties of foreign selection Apollo, Venus, and Kansas were the experimental material. It has been demonstrated that crop variety traits, weather and climatic conditions as well as soil tillage systems have the largest effect on yield capacity and thousand-seed weight. For example, in 2021, the average thousand-seed weight of Apollo variety was the smallest, and in 2022 – the largest and varied from 136.7 to 154.0 g. Under different soil tillage systems, this indicator made: 145 g – under the traditional plowing and no-till, 146 g – under deep loosening. It was determined that the average thousand-seed weight of Venus variety was larger both during the years (143.7, 172.3, and 155.3 g in 2021–2023, respectively) and soil tillage: 167 g – the traditional plowing, 155 g – deep loosening, and 149 g – no-till. The average thousand-seed weight of Kansas variety also had the corresponding tendency by the years (136.7, 159.7, and 151.7 g in 2021–2023, respectively) and changed depending on soil tillage: 152 g – under the traditional plowing, 151 g – under deep loosening, and 145 g – under no-till. Thus, the traditional plowing turned out to be the most effective for Venus and Kansas varieties, while there was no particular difference between soil tillage for Apollo variety. It was found that during the research years, the average soybean yield capacity varied in 2023 at the highest level, and in 2021 – at the lowest one and made: for Apollo variety 19.2–26.0 hundredweight/ha, Venus – 21.2–28.3 hundredweight/ha, and 20.3–29.5 hundredweight/ha for Kansas variety. Thus, almost the same average yearly yield (24.5–24.8 hundredweight/ha) was obtained from Venus and Kansas varieties, while it was by 7.8 % lower than in Apollo variety. It was determined that the following soil tillage systems were the most productive as to the average yearly soybean yields during the three years of the research: deep loosening for Venus variety (25.3 hundredweight/ha); the traditional plowing and deep loosening for Kansas variety (25.3–25.7 hundredweight/ha), and for Apollo variety – almost at the same level (22.4–23.0 hundredweight/ha).